THE SOURCES OF THE WORK “FUNUN ULBALAGHA” BY SHEIKH AHMAD TARAZI - Ibodullayeva Shalola O’tkir qizi (Western European Studies, 2025)
This article discusses the early treatise on Turkish linguistic prosody, “Funun ul-balagha” by Shaykh Ahmad Tarozi, focusing on its fourth section dedicated to prosody and the sources upon which it is based. In the creation of this treatise, Tarozi relied on works such as Mahmud Zamakhshari’s “Aruzi Qistos”, Andalusian’s “Aruzi Andalusiy”, and Nasiruddin Tusi’s “Meyar ul-ash’ar”. The article also explores how Tarozi continued the prosodic traditions and his unique approach to analyzing the metrical structure of poetry.
Keywords: Treatise; tradition; foundational sources